Sustainable Peatland Management Model-A Case of Kalampangan Village, Palangka Raya City, Central Kalimantan, Indonesia - Yulianti, N.; Adji, F.F.; Susetyo, K.E.; Kusin, K.; Naito, D. (International Information and Engineering Technology Association, 2023)
18 kilometers from Palangka Raya City, the capital of Central Kalimantan, Borneo’s part of Indonesia, Kalampangan is populated by farming communities who primarily produce important tropical crops. This former transmigrant village was occupied in the early 1980s, is located on peatland with a depth of approximately 4 meters. Peat is a vulnerable, spongy and acid soils. Recently, pressure from regulation and market demands for low carbon products has forced some local farmers to stop burnt and over-drainage and adapt their agricultural practices to more sustainable practices. The adoption rate, however, is still low. This study identifies the challenges and efforts towards sustainable management in Kalampangan’s agricultural communities, based on the information collected during a field visit, soil sampling and the discussion sessions, held with the selective farming and its community. The roles of the stake-holder through transformative leadership were shown to be very important for the shift from conventional to environmentally-friendly practices.